1996
DOI: 10.1016/s0741-5214(96)70103-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival after aberrant right subclavian artery–esophageal fistula: Case report and literature review

Abstract: Development of a fistula between an aberrant right subclavian artery and the esophagus is a rare cause of heretofore fatal hematemesis. We report the first known survivor of this devastating complication of the most common aortic arch anomaly. Intraoperative esophagogastroduodenoscopy, intraesophageal balloon tamponade, and arteriography were the keys to successful management. This lesion should be suspected in the setting of bright red, "arterial" hematemesis. Prolonged nasogastric and/or endotracheal intubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 27 publications
0
38
0
6
Order By: Relevance
“…[7] The diagnosis of ARSA aneurysm has an important clinical aspect due to the risk of spontaneous rupture and esophageal perforation. [8] Patients with an ARSA aneurysm may demonstrate an upper mediastinal widening on direct radiogram of the chest. [9] But since this is a non-specific finding, other entities must be brought to mind in the differential list, such as lymphadenopathy, substernal goiter, and enlarged aortic arch.…”
Section: Discussionmentioning
confidence: 99%
“…[7] The diagnosis of ARSA aneurysm has an important clinical aspect due to the risk of spontaneous rupture and esophageal perforation. [8] Patients with an ARSA aneurysm may demonstrate an upper mediastinal widening on direct radiogram of the chest. [9] But since this is a non-specific finding, other entities must be brought to mind in the differential list, such as lymphadenopathy, substernal goiter, and enlarged aortic arch.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of aortoesophageal fistula development in adult patients with congenital aortic arch abnormalities and prolonged nasogastric intubation has been previously reported. An extensive literature review showed an abundance of cases of congenital aortic arch abnormalities, including double aortic arch, and aortoesophageal fistula in the setting of prolonged nasogastric intubation in the pediatric population [4][5][6][7][8][9][10][11] , but only a few in the adult patient population [12][13][14][15][16][17][18] (Tables 1 and 2). …”
Section: Discussionmentioning
confidence: 99%
“…Origina-se como último ramo do arco aórtico logo após a artéria subclávia esquerda, cursa em direção ao braço direito, geralmente com localização retroesofágica (80%), mas pode localizar-se entre a traquéia e o esôfago (16%), ou anteriormente ao esôfago(4%) 12,13 . Pacientes com síndrome de Down apresentam essa anomalia em até 37% dos casos 14 .…”
Section: Discussionunclassified
“…Pacientes com síndrome de Down apresentam essa anomalia em até 37% dos casos 14 . Nessa série, todos os casos descritos eram retroesofágicos, três apresentavam síndrome de Down e houve predomínio do sexo feminino (67%), conforme descrito por Miller et al 13 A existência de arco aórtico direito, com artéria subclávia anômala esquerda sem ducto arterioso associado, embora rara, ocorreu em um de nossos casos 3 . Considerando que a artéria subclávia anômala geralmente comprime o esôfago em sua parede posterior, os sintomas digestivos predominam no quadro clínico, presentes em 73% dos nossos pacientes 3,15 .…”
Section: Discussionunclassified